Nanyang Technological University events management web application - Ang, Kok Jian (Nanyang Technological University, 2020)
This report documents the development and design process of the Final Year Project: Nanyang Technological University (NTU) Events Management Web application. All essential software development documents have been included to allow easy comprehension by the reader. This report contains five main chapters: Introduction, User Research and Interviews, Design and Implementation, Testing and Evaluation, Conclusion and Future Works. The first chapter is the Introduction which explains the rationale and motivation of embarking on the project, states the current limitations of available systems, describes the objective and scope of the project. The second chapter, Literature Review, compares similar web applications available on the market. The third chapter, User Research and Interviews, documents the process of obtaining essential user insights and feedback on current methods for events management by conducting one-to-one user interviews to better understand the current context of events management within NTU, possible areas of improvements and expectations from prospective users. The fourth chapter, Design and Implementation, is split into two main parts which consists of the design phase and the implementation phase. The design phase consists of all processes required to determine the overall user flow of the web application, use case scenarios and models as well as the overall front-end low fidelity wireframes and highfidelity user interface design prototypes of the actual web application. The implementation phase consists of detailed software development documents which explains the detailed codes used to implement important functions within the web application. The fifth chapter, Testing and Evaluation, consists of the product testing where tests are done to ensure that each individual unit functions and that as an overall system, the final product meets all functional requirements with their results recorded in a table form. This is followed by the User Acceptance Test where actual potential users get to test the system with their testing results and overall feedback recorded in a table form. The sixth chapter, Conclusion and Future Works, lists the overall development planning and scheduling of the project followed by possible future works that could be done to improve the web application. Finally, the key takeaways and learning points from the experience through the Final Year Project (FYP) serves as the conclusion to the report.